HUBUNGAN KADAR HEMOGLOBIN TERHADAP KAPASITI AEROBIK (STUDI KORELASI PADA ATLET WUSHU PRIMA 2014) - Novita Novita (Universitas Negeri Medan, 2015)
This research was aimed to determine the relationship between hemoglobin and aerobic capacity of wushuathletes of PRIMA in 2014. This was a descriptive quantitative research with laboratory test methods. Thepopulation in this research were wushu athletes of PRIMA entirely and only took 6 athletes to becomesamples. Based on the data analysis of data by non-parametric statistical method of SPERARMAN,obtainedcorrelation coefficient of 0.829 with a significant <0.05. The conclusions of this research: there is a positivecorrelation between the levels of hemoglobin to aerobic capacity of PRIMA’s Wushu Athletes in 2014.